The second formation of Islamic law : - Burak, Guy (Cambridge studies in Islamic civilization, 2015)
"The Second Formation of Islamic Law is the first book to deal with the rise of an official school of law in the post-Mongol period. The author explores how the Ottoman dynasty shaped the structure and doctrine of a particular branch within the Hanafi school of law. In addition, the book examines the opposition of various jurists, mostly from the empire's Arab provinces, to this development. By looking at the emergence of the concept of an official school of law, the book seeks to call into question the grand narratives of Islamic legal history that tend to see the nineteenth century as the major rupture. Instead, an argument is formed that some of the supposedly nineteenth-century developments, such as the codification of Islamic law, are rooted in much earlier centuries. In so doing, the book offers a new periodization of Islamic legal history in the eastern Islamic lands"-- Από τον εκδότη.